Acceptance and commitment therapy among caregivers of people with cancer: a systematic review and meta-analysis - Yunfan Gu; Mingyu Duan; Yanyan Huang; Maorong Hu; Mengjie Bao; Fang Yang (Scientific Reports)
Abstract To determine the effect of acceptance and commitment therapy (ACT) on improving the mental health of caregivers of cancer patients and to identify key intervention methods that enhance the efficacy of ACT. A computer search was conducted in PubMed, the Cochrane Library, CINAHL, Embase, Web of Science, CNKI, Wanfang, and Weipu, with the search period from the establishment of the database to July 31, 2024. Two researchers independently screened the literature, extracted the data, and assessed the quality of the included studies via RevMan 5.4 and Stata 14 software for meta-analysis. A total of 8 randomized controlled trials involving 675 caregivers were included. The effect size of ACT in improving mental health after intervention ranged from [SMD = −  0.41, 95% CI (− 0.59, − 0.23)] to [SMD = − 1.22, 95% CI (− 2.28, − 0.15)], and the effect size for mental health at follow-up ranged from [SMD = − 0.49, 95% CI (− 1.18, 0.20)] to [SMD = − 0.80, 95% CI (− 1.52, − 0.07)]. Subgroup analysis based on different outcome indicators revealed that ACT treatment in a hospital setting improved caregivers’ anxiety [SMD = − 1.45, 95% CI (− 1.72, − 1.15)], depression [SMD = − 1.07, 95% CI (− 1.89, − 0.25)], and increased psychological flexibility at follow-up [SMD = − 1.42, 95% CI (− 1.80, − 1.05)]. Using face-to-face intervention methods improved patients’ negative emotions (anxiety [SMD = − 1.44, 95% CI (− 1.72, − 1.15)], depression [SMD = − 1.07, 95% CI (− 1.89, − 0.25)], and psychological flexibility [SMD = − 1.42, 95% CI (− 1.80, − 1.05)]). Combining ACT with conventional psychological care further enhanced efficacy (anxiety [SMD = − 1.44, 95% CI (− 1.72, − 1.15)], depression [SMD = − 1.07, 95% CI (− 1.89, − 0.25)], and psychological flexibility [SMD = 0.33, 95% CI (0.15, 0.51)]). Additionally, the overall attrition rate for ACT treatment was low (18%), indicating a high acceptance of ACT among caregivers. Acceptance and commitment therapy can improve anxiety and depression in cancer caregivers, alleviate stress symptoms, and enhance their psychological flexibility. Moreover, caregivers show a high level of acceptance for this therapy, making it applicable in the psychological treatment of cancer caregivers.